Bulletin of the Iranian Mathematical Society - Ebrahimi Vishki, Hamid Reza.; Soleimani-damaneh, Majid; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
The Journal is a publication of the Iranian Mathematical Society in English. With six issues per year, the Journal publishes original research papers with significant contributions or of broad interest, and invited survey articles. High quality is critically pursued by the editorial body of the bulletin in the reviewing procedure of all submissions. The published article constitutes the final, definitive, and citable version of the work.
Keywords: Mathematics; Mathematics, general